(untitled) (The Pretoria Student Law Review, 2023)
This article aims to determine the most appropriate liability regime foraccidents caused by Autonomous Vehicles (AVs) resulting in personalinjury or death. The motivation for this research lies in the fact thatAVs are currently not adequately regulated within South Africanlegislation. Seeing as the regulation of AVs should begin sooner ratherthan later, it is essential to examine the capability of the Road AccidentFund (RAF) to provide for AVs and consider other possible liabilityregimes. The article will focus on the RAF Act and the possibility ofincluding the definition of AVs under section 1 thereof. The RAF Actcurrently defines a motor car as a motor vehicle designed or adaptedfor the conveyance of not more than ten persons, including the driver.The article will analyse the Civil Aviation Act (Aviation Act) to propose aregime where the owners of AVs are required to have private insurance.Section 8(5) of the Aviation Act will form the basis for the proposedregime change as this section holds that a registered owner or operatorof an aircraft must have insurance as prescribed for any damage or lossthat is caused by an aircraft to any person or property on land or water.